GAYA PENAMPILAN DAKWAH HANAN ATTAKI, ALI JABER, DAN MIFTAH - DIYA’ ANNISAUL FAUZIAH; SALAMAH NOORHIDAYATI (Universitas Islam Negeri (UIN) Mataram, 2021)
In preaching, da'i must need a way or method to provide attractiveness for the object of da'wah to enter into the study of da'wah, the ethics of fashion as a thing that is very noticed by the community in the da'wah of its da'i, no wonder when fashion trends today become a favorite thing of the community in a da'wah delivered by the da'i. It has been widely studied about the ethics of fashion in preaching in order to attract mad'u, but not all people have a fashion interest in one da'i. In this journal, the author took three examples of da'i using clothes that were able to attract mad'u in his da'wah studies, namely Hanan Attaki, Ali Jaber, and Miftah. The purpose of this journal is because the public knows that fashion is able to cause mad'u interest in a da'wah. With this journal, we will know that all kinds of clothing can be used as a trend of da'wah as long as it doesn’t violate ethics of da'wah fashion that is in accordance with shariat islam